BENTUK - BENTUK PARTISIPASI MASYARAKAT SEKITAR HUTAN TERHADAP KEAMANAN HUTAN ( KASUS DESA PELANG LOR, KEDUNGGALAR - NGAWI ) - Waliulu, A. Rachman (MAPETA, 2002)
Society participation is the urgent role in forest security. During the time, Perhutani had been co operate with "pesanggem", so that it is properly for it to get participation from society. The most participation who were done by "pesanggem' in Village Pelang Lor, Kedunglar Ngawi were contact, information, response participation and discuss about the effort to handle forest burning and breaking. The other side, the less participation was to handle and evaluate those.